ETHICAL CONCERNS IN USING OF GENERATIVE TOOLS IN HIGHER EDUCATION: CROSS - COUNTRY STUDY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Even though the historical development of artificial intelligence started in the mid-20th century, since the launching of Chat GPT this concept emerged in the scientific and educational agenda. Different concerns are arising at different education levels, starting from a discussion about whether should it be considered plagiarism, and ending with ethical aspects of the usage of Chat GPT by students and educators. The research aims to research the main recent scientific findings about generative tools in artificial intelligence and the ethical aspects of its usage in education. Methods used – analysis of recent scientific findings and statistical analysis of the answers of the respondents on authors created a survey for students of Higher Education Institutions about their attitudes and knowledge towards Generative Tools of Artificial Intelligence. Analysis was performed via SPSS comparing the opinion of students towards ethics of Generative Tools of AI from different countries. Results of the research show the attitudes of students towards the usage of Generative Tools of Artificial Intelligence from different countries.